Suicide Behavior Before and After the Start with Antidepressants: A High Persistent Risk in the First Month of Treatment Among the Young - Termorshuizen, Fabian (Int J Neuropsychopharmacol, 2015)
BACKGROUND: A causal relationship between antidepressants (ADs) and a high risk of suicidal behavior at a young age has been suggested. We analyzed the rates of suicide attempts during treatment with AD in comparison with the rates before treatment initiation for different ages. METHODS: Claims of insurance company Achmea were linked to the population registry of Statistics Netherlands. Episodes of AD use were defined for those with their first registered prescription in 2006–2011 (n = 66,196). Rates were analyzed in a Poisson model. Correlates of attempts in the first month of AD use were assessed in a logistic model. RESULTS: Among those aged <25 years, a high rate of suicide attempts during the month before the start of ADs was found (376.3/10 000 person yrs). A non-significant increase in the first month (p = 0.212) was found and a non-significant trend to lower values was determined thereafter (p = 0.3050). Among those ≧25 years, a clear decrease to lower rates immediately after the start was observed (p < 0.025). The highest rates of suicide were found among those >40 years during the first month. Female gender was, but treatment characteristics were not, associated with early attempts at a young age. CONCLUSIONS: Among young AD users, a high pre-treatment risk of suicide attempts was present and persisted during the early phases after the start. This contrasted with the clear decrease in risk among those aged ≧25 years, suggesting lower effectiveness of ADs to prevent suicidal behavior at young ages. Caution should be exercised to infer a causal relationship or to use data on attempts to predict risk of suicide during AD use.